The 15-Minute City: A Paradigm for Urban Planning and Policy - Omid Mobaraki (Sustainable Earth Trends)
The concept of 15-minute city (FMC) represents an urban planning and policy paradigm that seeks to focus the attention on the neighborhood as a place rather than a spatial and functional planning unit. The main premise of this concept is that urban services and amenities should be accessible within 15 minutes of walking or cycling from the residence. The principles of urban planning that enable the realization of the FMC include planning in mixed-use neighborhood units, proximity-based planning, transportation planning, citizen participation in planning and innovation, and smart planning. This innovative approach provides important findings and recommendations to the principles of urban planning of FMC, along with the issues of proximity-based planning, using the land and urban form, urban governance, and citizen participation. The aim of this study was examining the concept, characteristics and theoretical literature as well as the emerging themes for urban planning and policy making in the FMC. The FMC and its principles can help achieve sustainable development in environmental, social, and economic dimensions. The greater accessibility, reduce vehicle dependency, improve air quality, equitable planning decision, better health and well-being are the advantages FMC. However, the FMC can be criticized for its physical determination, feasibility in areas with low population density, difficulty in implementation, financing, not taking into account the different geographical features of cities, the conditions of not paying attention to the needs of different social groups, biodiversity, energy efficiency, and culture and heritage.